Avaliação do efeito do extrato aquoso de Chenopodium ambrosioides L. no controle de Meloidogyne spp. em tomateiro e estudo do ciclo de vida e de hospedeiros de M. konaensis - Maia, Laianny Morais (2019)
The root-knot-nematodes belonging to the genus Meloidogyne, constituted by the group of phytonematoids with greater economic importance in the world agriculture. The objective of the treatment of phytopathogenesis, the reduction of use of the nematicides, and the demenate extracts vegetables. The objectives of this work were: (1) to evaluate the in vitro and in vivo effect of the aqueous extract of C. ambrosioides leaves on hatching and mortality of juveniles of Meloidogyne spp. (2) investigate the storage time of actions in the preservation of the nematicidal activity of the extract; (3) to evaluate the effect of the aqueous extract on soil and immersion of infected plants in the control of Meloidogyne spp; (4) to evaluate the aqueous extract as a force inducer in the tomato in the control of M. incognita; (5) identify, through bioguided fractionation, classes of chemical substances present in C. ambrosioides with nematicidal action; (6) To study the life cycle and host range of a new species of gall nematode, M. konaensis. In vitro assays indicated the aqueous extract of C. ambrosioides at concentrations of 5% and caused hatching of juveniles of Meloidogyne spp by up to 99% and caused a J2 rate of 99.8%. The extract prepared with dry leaves stored for 70 days maintained a nematicidal activity. The application of the aqueous extract to the soil and the immersion of infected roots of tomato in the vegetal extract caused the reduction of M. incognita infection in up to 99.3% and 96%, respectively. The aqueous leaf extract of C. ambrosioides was applied 24 times before inoculation with the nematoid may have activated mechanisms of protection of tomato plants cv. Santa Clara, which caused M. incognita infection to be reduced by 43.76%. Bioguided fractionation of the aqueous extract of C. ambrosioides revealed that the active compounds against M. incognita are present in the aqueous fraction of the extract and that the lethal concentration of C. ambrosioides extract against M. incognita was 4.500 ppm. Studies on the biological aspects of M. konaensis have indicated that juvenile hatching (J2) and its infectivity in 'Santa Clara' tomato can be influenced by temperature. The life cycle of this nematode in tomato was 21 days and this species is able to infect species of the families Asteraceae, Brassicaceae, Caricaceae, Curcubitaceae, Fabaceae, Lamiaceae, Solanaceae. The information obtained in this research confirmed that the aqueous extract of C. ambrosioides is considered a promising natural product in the control of Meloidogyne spp.